Application of Rula and Catia V5 in Designing Ergonomic Tools For Cleaning Staff Performance Improvement - Nugroho Agung; Asrul Dahlan; Septi Ningrum (Jurnal Riset Ilmu Teknik, 2024)
Cleaning staff play an important role in maintaining environmental cleanliness, but most still use simple equipment with non-ergonomic working postures. This condition risks causing musculoskeletal disorders (MSDs) and reducing work productivity. This study aims to design an ergonomically-based tool for collecting trash and leaves that can improve the comfort and efficiency of sanitation workers. The method used is Rapid Upper Limb Assessment (RULA) to measure the level of work posture risk, combined with design analysis us-ing CATIA V5 software tailored to user anthropometric data. The results showed that the RULA score before using the tool was at level 5, indicating the need for immediate improvement. After design and simulation, the RULA score decreased to level 2, meaning that the risk of injury was significantly reduced. These findings prove that ergonomically-based tool design can reduce physical workload, minimize the risk of MSDs, and improve the work efficiency of cleaning staff. This research contributes to the development of ergonomic cleaning equipment innovations and can be used as a reference for the design of similar work tools in other sectors.